Design, development and fabrication of thiophene and benzothiadiazole based conjugated polymers for photovoltaics - Ratha, Radhakrishna (My University, 2018)
The content of this synopsis report entitled "Design, development and fabrication of thiophene and benzothiadiazole based conjugated polymers for photovoltaics" is divided into five chapters. In chapter 1 the respective research area, where design synthesis and fabrication of conjugated polymers, along with the scope and significance of the subsequent chapters are discussed. In chapter 2 photostability enhancement of P3HT-PCBM by using appropriate ratio of MWCNT in ambient conditions have been discussed. Chapter 3 discusses about synthesis of poly(ortho-arylene-vinylene) type of polymer alternating at 5,6-position of BT namely PI and P2 in the polymer main chain. Chapter 4 demonstrates that on functionalization of methyl acetate group at 5,6-positions of BT red-shift absorbance, lowered the LUMOOptical improves phase separation in active layer of PSC and hence improves solar cell performance compared to its methyl counterpart. Chapter 5 results in synthesis of newer napthothiadiazole (NT) based D-A polymer and their BHJ solar cell performance.
Iyer, Parameswar Krishnan
Keywords: NANOTECHNOLOGY